2023
DOI: 10.1002/ghg.2203
|View full text |Cite
|
Sign up to set email alerts
|

Study on the influence of water injection pressure on water absorption process and water injection effect of coal

Abstract: Rock burst disasters can be reduced and prevented with the help of coal dust water injection. In this study, the high‐pressure water injection device is used to examine how the water absorption rate changes over time under various water injection pressures. The results reveal that the water absorption rate of coal samples increases quickly initially before slowing down with water absorption time. Its change can be described using the Langmuir equation. In addition, the Langmuir equation is utilized to demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Coal is a dual medium containing cracks and pores, which serve as channels for the storage and transportation of solutions. 23 When a coal sample is immersed in a sodium chloride solution, the solution initially fills the holes and cracks. In the absence of an applied electric field, no electrical properties are observed.…”
Section: Resultsmentioning
confidence: 99%
“…Coal is a dual medium containing cracks and pores, which serve as channels for the storage and transportation of solutions. 23 When a coal sample is immersed in a sodium chloride solution, the solution initially fills the holes and cracks. In the absence of an applied electric field, no electrical properties are observed.…”
Section: Resultsmentioning
confidence: 99%
“…By substituting Equations ( 9) and (10) into Equation (8), we can obtain the governing equation (13) for the migration of the various gases in the cracks:…”
Section: Control Equation For Gas Migration In Fracturesmentioning
confidence: 99%
“…Zhang [11] , Wang [12] , and Yang [13] found that the gas flooding technology for CH4 extraction is more feasible in principle and effect than single-gas injection through a field application of single-gas injection to displace coal seam gas. Jia [14] , He [15] , and Fan [16] concluded that N2-ECBM and CO2-ECBM can significantly improve the CH4 extraction rate through a numerical simulation of single-gas flooding of a CH4-containing coal seam.…”
Section: Introductionmentioning
confidence: 99%